Multi-Representation-Based Recitation Program with Local Wisdom Loads to Improve Students' Concept Mastery on Newtonian Mechanics Topics - Taufiq, Briliantama Akbar; Purwaningsih, Endang (Jurnal Riset Pendidikan Fisika, 2022)
This study aims at exploring an increase in students' conceptual understanding of the topic of Newtonian mechanics after receiving a recitation program containing conceptual practice questions with contexts containing local wisdom and various representations, as well as describing difficulties in working on Newtonian mechanics questions. The research method used is the mix method - embedded experimental model with one group pretest and posttest design. The research was conducted on 20 students of class X. The instrument to measure students' conceptual mastery was in the form of 10 multiple choice questions and to measure the difficulties faced by students was an unstructured interview guide. The research data were analyzed using inferential tests so that the results showed that there were differences before and after the recitation program with a gain value of 0.60 in the medium category and the impact strength value of 1.87 in the high category. on students' mastery of concepts. The difficulties faced by students, in general, are interpreting physics symbols and understanding the meaning of the problem to determine the right equation to solve the problem. The implications of the research results on education are that it can be an alternative in increasing students' mastery of concepts and identifying student difficulties for evaluation to optimize the next learning process.Keywords: recitation program, multi representation, local wisdom, mastery of concepts AbstrakTujuan penulisan artikel ini adalah menganalisis peningkatan penguaaan konsep siswa pada topik mekanika newton setelah menerima program resitasi yang berisi soal latihan konseptual dengan konteks bermuatan local wisdom dan representasi beragam, serta mendeskripsikan kesulitan – kesulitan dalam mengerjakan soal mekanika newton. Metode penelitian yang digunakan yakni mix method - embedded experimental model dengan one group pretest and posttest design. Penelitian dilakukan pada 27 siswa kelas X. Instrumen untuk mengukur penguasaan konsep siswa berupa 10 soal pilihan ganda dan untuk mengukur kesulitan yang dihadapi siswa adalah pedoman wawancara tak terstruktur. Data penelitian dianalisis menggunakan uji inferensial sehingga didapatkan hasil terdapat perbedaan sebelum dan sesudah pemberian program resitasi dengan nilai gain 0,60 dengan kategori sedang dan nilai kekuatan dampak 1,87 dengan kategori tinggi, sehingga dapat disimpulkan terdapat pengaruh signifikan program resitasi berbasis multirepresentasi bermuatan local wisdom terhadap penguasaan konsep siswa. Kesulitan yang dihadapi siswa secara umum yaitu menginterpretasi simbol – simbol fisika dan memahami maksud dari soal untuk menentukan persamaan yang tepat untuk menyelesaikan soal. Implikasi hasil penelitian terhadap pendidikan yaitu dapat menjadi alternatif dalam meningkatkan penguasaan konsep siswa dan identifikasi kesulitan siswa guna evaluasi untuk mengoptimalkan proses pembelajaran selanjutnya.